Topographic characteristics of landslides induced by the 2015 Gorkha earthquake, Nepal (Journal of Nepal Geological Society, 2018)
The 2015 Gorkha earthquake and its aftershocks induced landslides in central Nepal. In this study, field surveys were conducted, and Google Earth satellite images were analysed for pre- and post-mainshock and aftershock scenarios to clarify the distribution of landslides. A total of 13,097 new landslides and 750 enlarged landslides were identified and mapped as polygon-based data over an area of 7.8 × 103 km2 between the epicenters of the main shock and the largest aftershock at the mountainous southern margin of the High Himalayas. Shallow-disrupted landslides were the most common type of mass movement. The areas of individual landslides ranged from 10 to 3.2× 105 m2, covering a cumulative area of 5.4 × 107 m2 or 0.7% of the study area. The landslide density was high in the Gorkha, Rasuwa, and Sindhupalchok districts, indicating that these areas suffered greater damage. Landslides occurred mainly on steep slopes (>35°) in V-shaped inner gorges, on geologically controlled steep slopes such as the scarp slopes (infacing slopes) of mountain ridges, and on terrace scarps. The results suggest that earthquake-induced landslides occur on slopes preconditioned by topographic and litho-structural factors. Based on our observations, recommendations for the mitigation of future landslide disasters are provided.